Green route synthesis of manganese oxide nanoparticles by using methanolic extract of Sapindus mukorossi (reetha) - Geetanjali Lohiya; Anshu Tamta; Bhuwan Chandra; Narain Kandpal; Rajendra Joshi (Journal of Water and Environmental Nanotechnology)
Nanoparticles of manganese oxide have been synthesized by a green chemistry approach using manganese chloride (MnCl2.2H2O), potassium permanganate (KMnO4), and methanolic extract of Sapindus mukorossi (reetha). In this study, we report here a simple ecofriendly green route to synthesize MnO2 nanoparticles. Manganese oxide nanoparticles were characterized by Fourier Transform Infra-Red (FTIR), UV-Vis spectral analysis, High-Resolution Transmission Electron Microscope (HRTEM), and Scanning Electron Microscope (SEM). The surface morphology showed that the MnO2 nanoparticles were uniformly dispersed. The average particle size was found 16 nm obtained by X-ray Diffraction (XRD), analysis. To find particle size DLS analysis has been done. The thermal stability of the nanoparticles with the temperature increase has been determined by Thermo-gravimetric Analysis (TGA) measurement. The synthesized manganese oxide nanoparticles were screened for antibacterial activities on gram-positive bacteria Staphylococcus aureus, Bacillus subtilis, and gram negative bacteria Pseudomonas aeruginosa, Escherichia coli. The results of the antibacterial study suggest that the manganese oxide nanoparticles can be useful for effective growth inhibitors in microorganisms with applications to medical devices and antimicrobial-controlled systems. The order of the reactivity towards zone of inhibition of microorganisms observed in the order of Escherichia coli (9mm) > Pseudomonas aeruginosa (8.3mm) > Bacillus subtilis (7.3mm) > Staphylococcus aureus (5.3mm).